THE RELATIONSHIP BETWEEN LEARNING ATTITUDES AND LEARNING OUTCOMES ON THE MATERIAL OF NEWTON'S LAW OF GRAVITY IN PUBLIC HIGH SCHOOL 2 SUNGAI PENUH CITY - Febriana, Nadia Yensi (Journal of Learning and Technology in Physics, 2024)
The purpose of this study was to determine whether there is a significant relationship between attitudes and learning outcomes in Newton's Law of Gravity material in class XI MIPA 2, XI MIPA 3, and XI MIPA 4 in SMA Negeri 2 Kota Sungai Penuh. This research is quantitative descriptive. The independent variable in this study is the attitude of the students, and learning outcomes are the dependent variable. The population taken was as many as 105 people consisting of class XII MIPA 2, XI MIPA 3, and XI MIPA 4 SMA Negeri 2 Sungai Penuh City and the sample taken was 50 people. Data collection techniques using a questionnaire (questionnaire). Data analysis techniques were carried out including normality test, linearity test, and correlation test with the help of SPSS 21 software. The test results obtained a Pearson correlation value of 0.518, meaning that there is a weak correlation between attitudes and learning outcomes with a Sig. (2-tailed) = 0.00 <0.05 then H0 is rejected, this means that H1 is accepted, that is, there is a significant relationship between attitudes and learning outcomes, although there is a linear correlation but the correlation is weak. Keywords: Attitudes, Learning Outcomes, Physics